A positive Living-in-History effect: the case of the fall of the Berlin Wall. Issue 10 (26th November 2019) - Camia, Christin; Menzel, Christina; Bohn, Annette
ABSTRACT: Research has shown that individuals use a combination of cultural life script events and historical events when dating personal memories, providing evidence for a cultural life script effect and Living-in-History (LiH) effect on the temporal organisation of autobiographical memory. Yet, in contrast to life script events, the LiH effect has only been found for negative events such as war or natural disasters. Therefore, this study tested whether a positive historical event, here the fall of the Berlin Fall, also elicits a LiH effect and whether this effect would differ due to the subsequent changes in life. Comparing West and East Germans, we found a moderate LiH effect for the fall of the Berlin Wall in East Germans but not in West Germans. Yet, the LiH effect in East Germans did not relate to the perceived change in life or the valence of the historical event. Additionally, this study replicated the finding that life script events serve as temporal landmarks when navigating through one's autobiographical timeline.